Pengembangan Metode CST (Communicative Swimming Training) Untuk Mengatasi Phobia Air Pada Anak Usia Dini - Centrum, Rizqi Suryawati (Journal of Sport Science and Education, 2019)
This study aims to develop a common communication between swimming trainers and students then poured into a method or procedure that can be used to overcome water phobia in early childhood, namely CST (communicative Swimming Training) method. CST method has 11 steps or steps that can be followed to overcome water phobia in early childhood. This method is given in a communicative manner in the form of seduction, using good words, firm and accompanied by basic swimming techniques to be used in children who experience water phobias. The effectiveness of this method is evidenced by the decrease in the percentage percentage of the amount of data in the subject I decreased by 39% and on the subject II there was a decrease of 42% taken from the difference between the data before and after the trial. This proves that this method can reduce water phobia experienced by early childhood and this method is more effective at an early age because emotional in early childhood can still be regulated than the age of pre-adolescence or about 9 years and above. The need for repetition of treatment that researchers provide to accelerate the healing of water phobias experienced by the child and do not forget to always pay attention to the health conditions of children who experience water phobia.